Spontaneous transformation and immortalization of mesenchymal stem cells in vitro - Popov, B V; Petrov, N S; Mikhaĭlov, V M; Tomilin, A N; Alekseenko, L L; Grinchuk, T M; Zaĭchik, A M (T͡S︡itologii͡a, 2009)
Mesenchymal stem cells (MXC) possess plasticity and unlimited proliferative activity in vitro that makes them an attractive subject of the studies focused on searching new resources for regenerative medicine. The usage of MSC is effective for treatment of patients with degenerative and traumatic diseases of different tissues, however, biological basis of therapeutic efficacy of MSC are still obscure. We found that long term culture of MSC expressing transgenic green fluorescence protein (GFP) led to increase in their proliferative activity, decrease in adhesion, and loss of differentiation potential and production of the GFP. MSC at the first passages showed karyotipic features of transformation, that at the later passages were complicated with developing of tumorigenic abilities detected after transplantation into normal syngenic recipients. When explanted into cell culture conditions the cells of the tumor tissue originated from the MSC did not express GFP and were not inducible to differentiation, but in contrast to the parent cells showed decreased clonogenic and proliferative activities. We suggest that growth of MSC in vitro results in their spontaneous transformation at early passages. Immortalization making physiological basis for the unlimited proliferation of MSC in vitro may be a feature of MSC transformation but not an initial characteristic of the stem cells.